2021
DOI: 10.1016/j.celrep.2021.109481
|View full text |Cite
|
Sign up to set email alerts
|

FBF1 deficiency promotes beiging and healthy expansion of white adipose tissue

Abstract: Highlights d Fbf1 tm1a/tm1a mice exhibit ''healthy obesity'' with healthy and beiging white fat tissue d FBF1 controls the beiging program via a cilia-specific, AKAP9-dependent, PKA signaling d FBF1 governs the adipogenic program via Hh signaling d Fbf1 tm1a/tm1a mice are protected from diabetes and show reduced risk of dying prematurely

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 51 publications
(68 reference statements)
0
15
0
Order By: Relevance
“…However, it can be surmised that this cross-talk has consequences beyond the regulation of cell metabolism, such as cell differentiation and major physiological processes such as memory acquisition. In line with this assumption, both the primary cilium and autophagy are engaged in white adipocyte differentiation (Singh et al, 2009b;Zhang et al, 2009;Hilgendorf et al, 2019;Zhang et al, 2021) and are known to be involved in hippocampal memory acquisition (Glatigny et al, 2019;Jovasevic et al, 2021;Bashford and Subramanian, 2022). Whether or not the primary cilium and the autophagic pathway communicate during these processes is still an open question.…”
Section: Discussionmentioning
confidence: 99%
“…However, it can be surmised that this cross-talk has consequences beyond the regulation of cell metabolism, such as cell differentiation and major physiological processes such as memory acquisition. In line with this assumption, both the primary cilium and autophagy are engaged in white adipocyte differentiation (Singh et al, 2009b;Zhang et al, 2009;Hilgendorf et al, 2019;Zhang et al, 2021) and are known to be involved in hippocampal memory acquisition (Glatigny et al, 2019;Jovasevic et al, 2021;Bashford and Subramanian, 2022). Whether or not the primary cilium and the autophagic pathway communicate during these processes is still an open question.…”
Section: Discussionmentioning
confidence: 99%
“…Genetics may also influence WAT distribution [ 72 ]. Recently, Fas Binding Factor 1 (FBF1) deficiency has been shown to stimulate beiging and beneficial growth of WAT [ 73 ]. Interestingly, FBF1 controlled the beiging program via a cilia-specific, A-kinase anchoring protein (AKAP9)-dependent, protein kinase A (PKA) signaling, supporting a central role for primary cilia in the fate determination of preadipocytes and the generation of metabolically healthy adipose tissue [ 73 ].…”
Section: Potential Role Of Adipose Tissuementioning
confidence: 99%
“…Genetic manipulations of MSCs and pre-adipocytes have revealed that the primary cilium can both inhibit and promote adipogenesis. Specifically, depletion of BBS12, FBF1, or PKD1 promotes adipogenesis, while depletion of ALMS1, KIF3A, or IFT88 inhibits adipogenesis ( Marion et al, 2009 , 2012 ; Zhu et al, 2009 ; Huang-Doran and Semple, 2010 ; Qiu et al, 2010 ; Zhang et al, 2021 ). Notably, we recently showed that genetic ablation of ciliation specifically in pre-adipocytes of adult male and female mice, via the depletion of Ift88 using a tamoxifen-inducible Pdgfr α-CreERT, completely prevented in vivo adipogenesis ( Hilgendorf et al, 2019 ).…”
Section: Primary Cilia Direct How White Adipose Tissue Expandsmentioning
confidence: 99%
“…Since the BBSome is required for ciliary removal of receptors, we postulate that loss of BBSome function results in ciliary remodeling in MSCs, which in turn results in increased adipogenic commitment and/or increased recruitment of MSCs to white adipose tissue. Similarly, mouse models deficient for Fbf1 , which can regulate ciliary entry and exit by ensuring proper BBSome assembly, are obese with improved glucose and insulin tolerance, in part due to increased white adipose tissue hyperplasia and beiging ( Zhang et al, 2021 ). Mouse models deficient for Pkd1 , which encodes the protein polycystin-1 and is commonly mutated in autosomal dominant polycystic kidney disease, have skeletal abnormalities, and isolated MSCs and primary osteoblasts have a decreased osteogenic but increased adipogenic potential ( Qiu et al, 2010 ).…”
Section: Primary Cilia Direct How White Adipose Tissue Expandsmentioning
confidence: 99%